Histidine-Rich Protein 2 Plasma Levels Predict Progression to Cerebral Malaria in Malawian Children With Plasmodium falciparum Infection - Fox, Lindsay L. (Oxford University Press, 2013)
Some children with uncomplicated malaria progress to cerebral malaria despite appropriate treatment; identifying them in advance might improve their care. The objective of this study was to determine if plasma concentrations of a malaria protein, HRP2 (histidine-rich protein 2) would serve this purpose. Cases and controls were children presenting with uncomplicated malaria; the cases (n = 25) developed cerebral malaria, and the controls (n = 125) did not. Mean plasma HRP2 concentrations were significantly higher in the cases, and an HRP2 cutoff was identified that could predict disease progression (sensitivity and specificity, 88% for each). Quantitative measurements of HRP2 may be a useful screening tool.